Assessment of Components of Primary Health Services and Psychology Health Providers in Main Primary Health Care in the Kurdistan Region of Iraq - Shaho Osman Mahmood, Fatah Hama Rahim Fatah, Ary Hama Saeed Hama Salih (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Background: Primary health care (PHC) issue is trying to promote the best possible health and well-being for all individuals, regardless of their background, by focusing on the community's needs for sustainable and affordable healthcare. Objective: The primary goal of this study is to assess the key elements of primary healthcare services in the PHC centers located in the Kurdistan Region of Iraq. Methods: It is a mass cross-sectional observational study including PHCs in the Kurdistan region, Iraq. Sampling is done using multistage sampling that includes simple random sampling, stratified random sampling, and systematic random sampling design. The required PHC data were collected in Sulaymaniyah, Halabja, Erbil, and Duhok governorates. The method of data collection involves visiting all primary healthcare centers and obtaining prior permission from the health directorate in each governorate. Face-to-face interviews with medical personnel will be conducted, and a standardized checklist will be used to evaluate health service indicators. Results: Out of a total of 222 primary healthcare centers in the Kurdistan region, we chose to focus on 68 main primary healthcare centers for this study. Child growth monitoring was the most frequently offered service, available at 77.3% of primary healthcare centers. Laboratory services were the next most common, with 76.7% providing them. Antenatal care was offered at 75.5% of centers, while child immunization services were available at 73.5%. Conclusion: Monitoring a child's growth is a crucial measure for promoting their survival. To improve the effectiveness of current primary healthcare centers, prioritizing laboratory services, and improving the staff's attitudes and practices are essential.